How the Grinch stole Christmas - Seuss, Dr. (New York : Random House, 1957)
The Grinch, whose heart is two sizes too small, hates Who-ville's holiday celebrations, and plans to steal all the presents to prevent Christmas from coming. To his amazement, Christmas comes anyway, and the Grinch discovers the true meaning of the holiday.
Keywords: Christmas stories; Christmas -- Fiction; Stories in rhyme